Malignant Spindle Cell Tumor of the Breast: Differentiating between Metaplastic Carcinoma and Malignant Phyllodes Tumor - Rosdiana, Yusfita Efi; Rahmadiani, Nayla (http://dharmais.co.id/, 2025)
Background: Spindle cell lesions of the breast include both benign and malignant tumors, with metaplastic carcinoma (MBC) and malignant phyllodes tumor (MPT) being the key malignant entities requiring differentiation due to distinct treatment strategies and prognoses. MBCs are rare, aggressive triple-negative breast cancers with significant histological and molecular heterogeneity. They often harbor TP53, PIK3CA, and EGFR mutations and are believed to arise from epithelial precursors. MBCs require wide surgical margins (radical mastectomy), and standard chemotherapy is often ineffective due to tumor heterogeneity. In contrast, MPTs are fibroepithelial tumors with a characteristic leaf-like growth pattern and originate from stromal–epithelial interactions. They are primarily treated with wide surgical excision (simple mastectomy), with limited evidence supporting adjuvant therapy. Malignant progression in MPTs is linked to TP53, MED12, and EGFR mutations, along with chromosomal abnormalities such as 1q gain. Differentiating MBC from MPT is challenging due to overlapping histological and immunohistochemical features. MBCs typically express epithelial markers like cytokeratin and p63, while MPTs show stromal overgrowth with minimal epithelial marker expression. Although advanced imaging techniques like MRI can assist in diagnosis, histopathological and immunohistochemical evaluation remain crucial. This article is a structured narrative literature review, synthesizing current evidence from peer-reviewed studies retrieved through a targeted search of PubMed, Scopus, and Web of Science without year restriction, prioritizing recent publications. The findings are organized into clinical, histopathological, immunohistochemical, and molecular aspects to facilitate accurate differentiation between MBC and MPT. In conclusion, integrating clinicopathological, immunohistochemical, and molecular data is essential for distinguishing these rare tumors, as they differ in pathogenesis, treatment approaches, and prognosis, thereby guiding optimal patient management.